Pleiotropic effect of LRRK2 on Parkinson‐associated proteins and processing of pathological alpha‐synuclein in myeloid cells. (20th December 2022) - Nykanen, Niko‐Petteri; Yang, Chengran; Harari, Oscar; Davis, Albert A; Cruchaga, Carlos; Benitez, Bruno A.
Abstract: Background: Mutations in the LRRK2 gene, which encodes leucine‐rich repeat kinase 2 (LRRK2), are a cause of autosomal dominant Parkinson's disease (PD). Single‐nucleotide polymorphisms (SNP) in the LRRK2 locus are one of the most consistently replicated in multiple genome‐wide association studies in sporadic PD and with inflammatory diseases. We recently found that a PD‐associated risk SNP (rs76904798, p = 2.0×10 −28 ) in the LRRK2 locus is also associated with cerebrospinal fluid (CSF) levels of granulins ( PGRN, p = 8.6×10 −9 ), glycoprotein nmb ( GPNMB, p = 2.3×10 −9 ), Ectonucleoside triphosphate diphosphohydrolase‐1 ( ENTPD1, p = 2.3×10 −9 ) also known as CD39 and Cathepsin B ( CTSB, p = 2.5×10 −4 ). Yet, functional validation in cellular models is lacking. Methods: Human monocytic cells (U937) were differentiated (dU937) into macrophages to test the effect of LRRK2 on CTSB, CD39, GPNMB, PGRN and alpha‐synuclein (aSyn). LRRK2 kinase activity and expression level were modulated using pharmacological inhibitors and lentivirus‐mediated overexpression. Protein levels were assessed using western blotting and ELISA. dU937 cells were treated with human aSyn pre‐formed fibrils (haSyn PFFs). We analyzed CSF somaLogic data from the Parkinson's Progression Marker's Initiative (PPMI) cohort (Data accessed November 2021). Results: LRRK2 mutation (G2019S and R1441G) carriers from the PPMI cohort exhibit significantly increased CSF levels of PGRN (p = 2.1×10 −22 ), GPNMB (p = 1.6×10 −29 ), CTSB (p = 2.5×10 −16 ) and CD39 (p = 1.8×10 −18 ) compared to age and gender‐matched non‐carriers (N = 1158). dU937 cells overexpressing LRRK2 showed an increase in the phosphorylation of LRRK2‐Ser935 and Rab10‐T73 and intracellular levels of lysosomal proteins CTSB and Saposin D without affecting LAMP1 or M6PR. LRRK2 also reduced extracellular CD39, PGRN and GPNMB levels and the levels of intracellular endogenous aSyn dimers in dU937 cells. HaSyn PFF treatment induced a time‐dependent reduction of CTSB and GPNMB levels, increased PGRN levels and altered intracellular aSyn processing pattern in dU937 cells overexpressing LRRK2. Pharmacological LRRK2 kinase inhibition decreased intracellular CTSB levels. LRRK2 co‐immunoprecipitates with PGRN in cells and in human brain. Conclusions: LRRK2 modifies lysosome‐associated proteins and regulate aSyn proteostasis. Pathogenic LRRK2 mutations increased CSF levels of PGRN, GPNMB, CTSB and CD39 in the PPMI cohort. Our in vivo and in vitro data supports a pleotropic role of the LRRK2 locus as a genetic modifier of PD‐associated proteins.